SOIL STABILIZATION (SUBGRADE) FOR AINARO LOT 2 ROAD PAPER, TIMOR – LESTE - Pedro Adelio Verona Soares; Sapto Budy Wasono (Neutron, 2023)
Soil conditions in Timor Leste vary greatly in terms of grain and bearing capacity. The soil found at the laulara solerema location is clay because it can be seen from various types of samples and the results of analysis in the laboratory can determine the quality of the soil and the type of soil. This study aims to determine the characteristics of clay soil in Laura – Solerema as a road pavement material, especially the soil foundation The method used in determining the mixture through several tests, among others, sieve analysis test, compaction test (standard proctor) CBR (California Bearing Ratio) test, Swelling, Atterberg limit test and compaction test. The results of testing the clay soil in Laura – Solerema partially have values that do not meet the requirements as road pavement materials, especially subgrade layers. The stabilization study aims to study and determine the results of soil test data, to be able to determine the optimum moisture content (OMC) and dry volume (MDD), and the Atterberg limit with CBR values of 95% and 100%.